Attitudes of Palestinians EFL Students Towards the Use of Jigsaw Cooperative Learning Technique in Teaching Reading Comprehension - Enas A. A. Abuhamda; Ramiaida Binti Darmi; Hazlina Abdullah (Psychology and Education, 2024)
Reading comprehension plays a crucial role in developing the reading skills. Therefore, reading comprehension is one of the most significant skills of all the four linguistic abilities, towards better effectively communication in classroom. Subsequently, the English Language (EL) teachers should consider and find different teaching methods in their classrooms in order to improve the language abilities of their learners in the classrooms such as Jigsaw Cooperative Learning Technique (JCLT) through changing their methods, materials and overcoming the traditional way of teaching English language. The aim of the study was to investigate Palestinians EFL secondary students’ attitudes towards the use of JCLT in teaching reading comprehension. In addition, the study adopted fully quantitative research design to collect data through the self-designed questionnaire survey that distributed randomly on a sample of 1094 Palestinians EFL secondary teachers in 2019-2020. The collected data were analyzed and treated statistically using SPSS.24. The results of the study showed that Palestinians EFL secondary students have positive attitudes towards using jigsaw cooperative learning technique as a tool in the EFL teaching. The recommendation and suggestion for studies were suggested in light of the findings.